2020
DOI: 10.3126/jbmr.v3i1.31973
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Characteristics on Organizational Commitment: The Role of Growth Need Strength in Nepali IT Companies

Abstract: Organizational commitment is one of the critical problems faced by the organizations, today. The outcomes related to commitment i.e. turnover and absenteeism can be resolved through enriched jobs. However, there is limited knowledge availability both from practical and academic aspects regarding the effect of job characteristics on organizational commitment, and keeping this perspective in mind this study examined the effect of job characteristics on organizational commitment in Nepali IT companies along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Committed employees will show their voluntary behavior and have a strong desire to serve their organization to pay for the effort in providing awareness for organizational goals beyond passive loyalty (Ismail, 2019). Organizational commitment helps employees identify their goals with the company and motivates employees to stay in it (Saud, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Committed employees will show their voluntary behavior and have a strong desire to serve their organization to pay for the effort in providing awareness for organizational goals beyond passive loyalty (Ismail, 2019). Organizational commitment helps employees identify their goals with the company and motivates employees to stay in it (Saud, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The level of autonomy given to an employee indicates the level of trust and value placed on the employees' creative values and prowess, Ogbor et al (2021) posited that autonomy as a degree of freedom can create room for creativity and innovativeness. Many scholars noted the significant role of a committed workforce as an asset and vital resource for organizations to gain a competitive edge and strong values (Nguyen et al, 2014;Saud, 2020). Exceptionally gifted employees are the intellectual capitals who are the key drivers of organizational performance and goal attainment beyond limits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shrestha and Parajuli (2020) revealed that the organizational commitment of employees is predicted by supervisory support/ behavior. Saud (2020) documented that job characteristics have significant positive effects on organizational commitment. Pandey (2020) reported that there is a positive relationship between work-life balance and employee commitment.…”
Section: Theoretical Framework and Review Of Literaturementioning
confidence: 99%